2022
DOI: 10.1038/s41598-022-15155-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in rumen microbiota via oral fiber administration during early life in dairy cows

Abstract: Bacterial colonization in the rumen of pre-weaned ruminants is important for their growth and post-weaning productivity. This study evaluated the effects of oral fiber administration during the pre-weaning period on the development of rumen microbiota from pre-weaning to the first lactation period. Twenty female calves were assigned to control and treatment groups (n = 10 each). Animals in both groups were reared using a standard feeding program throughout the experiment, except for oral fiber administration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Weaning calves from liquid to solid has shown rapid changes in their rumen microbiota [12,13]. However, fewer studies have reported the effect of age on the rumen microbial community of the host animal in the ruminant after weaning [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Weaning calves from liquid to solid has shown rapid changes in their rumen microbiota [12,13]. However, fewer studies have reported the effect of age on the rumen microbial community of the host animal in the ruminant after weaning [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the pattern remained the same. General rumen‐specific bacteria such as Acidaminococcaceae or the phylum Spirochaetes (Savin et al, 2022 ; Snelling et al, 2019 ) and bacterial families contributing to milk production in cattle such as Muribaculaceae and p‐251‐o5 (Boggio et al, 2021 ; Kodithuwakku et al, 2022 ) were considered to distinguish individual wildebeests. In contrast, bacterial families that only occurred in single individuals or that varied greatly among individuals were found by the LASSO algorithm to cluster individual microbiota (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the pattern remained the same. General rumen-specific bacteria such as Acidaminococcaceae or the phylum Spirochaetes (Savin et al, 2022;Snelling et al, 2019) and bacterial families contributing to milk production in cattle such as Muribaculaceae and p-251-o5 (Boggio et al, 2021;Kodithuwakku et al, 2022)…”
Section: Lasso Identified Features For Clustermentioning
confidence: 99%
“…Additionally, the presence of Muribaculaceae family members has been related to a lower incidence of diarrhea in neonatal calves [ 53 ]; besides, they can degrade complex polysaccharides and potentially produce short-chain fatty acids such as acetate, propionate, and butyrate [ 54 ]. According to Kodithuwakku et al [ 55 ], Muribaculaceae in the rumen contribute to efficient feed conversion into energy sources for milk production in dairy cows. Furthermore, the increase in the Succinivibrionaceae members’ family has been reported as promoters for establishing the early rumen microbiota of young calves [ 56 ].…”
Section: Discussionmentioning
confidence: 99%